Understanding agriculture in the climate negotiations: Preparing for SB58 - Chevallier, Romy; Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This briefing note, prepared for the 58th session of the UNFCCC Subsidiary Bodies (SBI and SBSTA) June 5-15 2023 (Bonn, Germany) provides the context of agriculture and food security in climate negotiations and achievements between 2011-2022 highlighting the joint work on inter-related topics between 2018 and 2020 (Koronivia, adaptation and resilience building, soil health and soil carbon storage through water management; nutrient use and manure management, improved livestock management systems, and intersections of the socioeconomic and food security dimensions of climate change in agriculture). The document lays out the objectives of the Sharm el-Sheikh joint work (2022) and key COP27 decisions and engagement opportunities for the East Africa Farmers Federation (EAFF) as well as queries for consideration by EAFF on modalities for implementation, topics and ideas around a user friendly portal for farmers' organizations and the type of information it would include. The brief further describes the African Group of Negotiators, the Global Stock Take (GST) , the AGNES pre-SB58 meeting objectives and messaging on farmer engagement in climate discussions.